Characteristics of Minor Ions and Electrons in Flux Transfer Events Observed by the Magnetospheric Multiscale Mission. Issue 7 (20th July 2020) - Petrinec, S. M.; Burch, J. L.; Chandler, M.; Farrugia, C. J.; Fuselier, S. A.; Giles, B. L.; Gomez, R. G.; Mukherjee, J.; Paterson, W. R.; Russell, C. T.; Sibeck, D. G.; Strangeway, R. J.; et al.
Abstract: In this study, the ion composition of flux transfer events (FTEs) observed within the magnetosheath proper is examined. These FTEs were observed just upstream of the Earth's postnoon magnetopause by the National Aeronautics and Space Administration (NASA) Magnetospheric Multiscale (MMS) spacecraft constellation. The minor ion characteristics are described using energy spectrograms, flux distributions, and ion moments as the constellation encountered each FTE. In conjunction with electron data and magnetic field observations, such observations provide important contextual information on the formation, topologies, and evolution of FTEs. In particular, minor ions, when combined with the field‐aligned streaming of electrons, are reliable indicators of FTE topology. The observations are also placed (i) in context of the solar wind magnetic field configuration, (ii) the connection of the sampled flux tube to the ionosphere, and (iii) the location relative to the modeled reconnection line at the magnetopause. While protons and alpha particles were often depleted within the FTEs relative to the surrounding magnetosheath plasma, the He + and O + populations showed clear enhancements either near the center or near the edges of the FTE, and the bulk plasma flow directions are consistent with magnetic reconnection northward of the spacecraft and convection from the dayside toward the flank magnetopause. Key Points: Long‐duration magnetosheath FTEs observed under at postnoon local times and under similar solar wind conditions are compared and contrasted Minor ions from the magnetosphere are observed at higher energies at the edges than at the center of the FTEs The cores of the magnetosheath FTEs are on closed field lines